PENGEMBANGAN MEDIA KOMIK 360 DERAJAT BERBASIS RELIGIOUS MODERATION CHARACTER PADA SISWA SEKOLAH DASAR UNTUK MEWUJUDKAN INDONESIA EMAS TAHUN 2045 - Reky Lidiana Banu; Maria Lodika Long; Oktavianus, Melki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The development of 360-degree comic media based on religious moderation character for elementary school students is a significant innovation in supporting the vision of Indonesia Emas 2045. This media is designed to foster a generation that is tolerant, inclusive, and has a strong sense of national identity from an early age, in line with the increasing complexities of modern times. According to media experts, the comic received a feasibility score of 92%, indicating high quality in terms of design, visuals, and navigation. Meanwhile, subject matter experts rated it 88%, signifying that the comic's content aligns well with curriculum requirements and is effective in supporting educational objectives. The effectiveness of this media was tested through research involving control and experimental groups, with statistical results showing a significance value greater than 0.05. This confirms that the use of the 360-degree comic has a significantly positive impact on students' understanding and internalization of religious moderation. The media not only captures students' attention but also enhances their comprehension of the importance of a moderate attitude in religious life. Therefore, the 360-degree comic has proven to be feasible, effective, and practical as a learning tool for developing religious moderation character in elementary school students, contributing to the achievement of the Indonesia Emas 2045 vision.